Absence of Drug‐Drug Interaction of Anastrozole on Levonorgestrel Delivered Simultaneously by an Intravaginal Ring: Results of a Phase 2 Trial. (21st February 2019) - Nave, Rüdiger; Mellinger, Uwe; Klein, Stefan; Höchel, Joachim; Schmitz, Heinz
Abstract: Intravaginal rings (IVRs) are an established option for continuous administration of drugs in women. The combination of anastrozole (ATZ) and levonorgestrel (LNG) in an IVR with an intended 4‐week wearing period has been considered for long‐term treatment of endometriosis‐associated pelvic pain. A randomized, parallel‐group, multicenter phase 2b study to assess the efficacy and safety of different dose combinations in women with symptomatic endometriosis has recently been performed. This paper will focus on the investigation of pharmacokinetic (PK) effects of ATZ on LNG using data collected from this study. Two hundred sixteen patients were randomized to the treatment group with IVRs releasing LNG 40 μg/day alone or in combination with ATZ 300 μg/day, 600 μg/day, or 1050 μg/day for 12 weeks. PK blood samples were taken before dosing and before IVR replacement or removal (days 28, 56, and 84). The primary PK parameter was the plasma concentration in apparent steady state of ATZ and LNG at the end of each IVR wearing period. Results of PK analysis demonstrate that ATZ concentrations increased proportionally with increasing dose (geometric mean values of 7.85, 15.48, and 22.61 μg/L at 300, 600, and 1050 μg/day nominal release, respectively). All point estimates for LNG concentration in apparent steady state ratios between the mono and combination IVR groups were close to 1, and the 90% confidence interval limits were in the 0.80 to 1.25 range (1.01 [0.85‐1.19], 1.03 [0.88‐1.20], 0.94 [0.80‐1.10]). In conclusion, our data indicate there is no evidence of drug‐drug interaction of ATZ on LNG.